2019
DOI: 10.1007/s13311-019-00730-7
|View full text |Cite
|
Sign up to set email alerts
|

PDZ Scaffold Protein CAL Couples with Metabotropic Glutamate Receptor 5 to Protect Against Cell Apoptosis and Is a Potential Target in the Treatment of Parkinson's Disease

Abstract: Targeting mGluR5 has been an attractive strategy to modulate glutamate excitotoxicity for neuroprotection. Although human clinical trials using mGluR5 negative allosteric modulators (NAMs) have included some disappointments, recent investigations have added several more attractive small molecules to this field, providing a promise that the identification of more additional strategies to modulate mGluR5 activity might be potentially beneficial for the advancement of PD treatment. Here, we determined the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Glutamate is an essential molecule for cells, especially cancer cells due to its paracrine effect on intracellular and extracellular communications where even the small changes in its levels significantly impact the cellular transformation and cancer progression [ 99 , 100 , 101 ]. The extracellular glutamate is mainly required for intercellular communication and activation of survival pathways, like the MAPK and PI3K pathways, promoting growth and invasion [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate is an essential molecule for cells, especially cancer cells due to its paracrine effect on intracellular and extracellular communications where even the small changes in its levels significantly impact the cellular transformation and cancer progression [ 99 , 100 , 101 ]. The extracellular glutamate is mainly required for intercellular communication and activation of survival pathways, like the MAPK and PI3K pathways, promoting growth and invasion [ 101 , 102 ].…”
Section: Discussionmentioning
confidence: 99%
“…Metabotropic glutamate receptor 5, named GRM5, has been shown to activate phospholipase C and participate in multiple biological processes [16]. Many studies have shown the Wnt/β-catenin signaling pathway participant into the osteogenic differentiation of ADSCs.…”
Section: Introductionmentioning
confidence: 99%
“…In primary cultured neurons, knockdown of Gopc expression by shRNA does not affect the abundance of its associated membrane proteins (Nlgn1, NMDA receptors, and mGlu5 were tested here). Instead, for two verified interaction partners of Gopc, namely, mGlu5 [ 22 , 23 ] and Nlgn1 [ 6 , 32 ], we observed that knockdown of Gopc reduces the amount of protein that is present at the cell surface. In the second set of experiments, we used a mouse line with a conditional deletion of the Gopc gene coding for Gopc in mouse forebrain neurons.…”
Section: Discussionmentioning
confidence: 91%
“…However, which part of the sorting machinery specifically is affected by Gopc has been a subject of debate, as it may be receptor- and cell type-specific [ 18 20 ]. Thus, for the CFTR, it has been proposed that Gopc contributes to its degradation in lysosomes [ 8 , 10 , 21 ], whereas for mGlu5 it was reported that degradation of the receptor by the ubiquitin/proteasomal system is prevented by Gopc [ 22 , 23 ]. A more common finding has been that overexpression of Gopc leads to retention of its associated membrane proteins at the TGN [ 12 , 17 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%